The Use of Conditioning Open-Label Placebo in Opioid Dose Reduction: A Case Report and Literature Review - Estudillo-Guerra, Maria A.; Mesia-Toledo, Ines; Schneider, Jeffrey C.; Morales-Quezada, Leon (Frontiers in Pain Research, 2021)
Introduction: Adequate pain management for inpatients in rehabilitation units is essential for achieving therapeutic goals. Opioid treatments are commonly prescribed, but these are associated with numerous adverse effects, including the risk of addiction and decreased quality of life. Conditioning an open-label placebo is a promising approach to extend the analgesic effect of the opioid while reducing its overall dosage. Objectives: To describe a patient's experience in using conditioning open-label placebo (COLP) as a pharmaco-behavioral intervention to decrease opioid intake and its side effects after inpatient rehabilitation discharge, and to perform a literature review about the use of open-label placebo in pain. Methods: This case study has been extracted from a clinical trial initiated in 2018. A 61-year-old male was recruited at a tertiary rehabilitation hospital after suffering a traumatic sport-related injury and orthopedic surgery. Pain management included prescription of non-steroidal anti-inflammatory drugs (NSAIDs) and short-acting oxycodone. After trial participation, the patient requested off-label COLP treatment to help him decrease outpatient opioid utilization. Results: After COLP treatment, the patient could discontinue oxycodone intake (a reduction from 15 morphine equivalents/day) after rehabilitation discharge. Moreover, opioid side effects decreased from 46 to 9 points on the numerical opioid side-effects scale. A literature review identified five clinical trials using “honest” open-label placebo (OLP) or COLP as an experimental intervention for pain control. From these studies, two were in the area of chronic lower back pain, one in post spine surgery, one in irritable bowel syndrome, and another in spinal cord injury and polytrauma. Four studies reported positive outcomes related to pain control, while one study showed no significant differences in pain management between treatment-as-usual and the COLP group. Conclusion: The case report illustrates how a pharmaco-behavioral intervention can facilitate downward opioid titration safely after inpatient rehabilitation. It initiates a discussion about new approaches for opioid management using conditioning and the patient's expectation of pain relief.